2015
DOI: 10.1139/cjpp-2014-0364
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the usefulness of thromboxane-A2modulation in the treatment of bronchoconstriction in asthma

Abstract: Airway smooth muscle (ASM) is the effector cell in the bronchoconstrictory pathway. It is believed that the bronchoconstriction present in asthma is associated with changes in the airway milieu that affect ASM excitation-contraction coupling and Ca(2+)-handling. Asthmatics also react differently to ventilatory mechanical strain. Deep inspiration (DI), which produces bronchodilation in healthy individuals, is less effective in asthmatics, and even enhances bronchoconstriction in moderate to severely affected pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 97 publications
(141 reference statements)
0
15
0
Order By: Relevance
“…While TxA2 synthetase inhibitors and TP receptor antagonists were found to have positive effects on allergic asthma in Japan [109], studies from Western countries revealed no obvious curative effects. This discrepancy may be associated with the genetic polymorphism in TxA2 synthetase and TP receptors [108].…”
Section: Antiplatelet Therapies For Asthma Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…While TxA2 synthetase inhibitors and TP receptor antagonists were found to have positive effects on allergic asthma in Japan [109], studies from Western countries revealed no obvious curative effects. This discrepancy may be associated with the genetic polymorphism in TxA2 synthetase and TP receptors [108].…”
Section: Antiplatelet Therapies For Asthma Controlmentioning
confidence: 99%
“…In allergic asthma, TxA2 causes bronchial contraction, increased vascular permeability, tissue edema, and airway hyperresponsiveness [107]. Blocking TxA2 synthesis reduces the concentration of TxA2 during asthma attacks, but another bronchoconstrictor, prostaglandin, which acts together with TxA2 by binding to the TxA2 receptor (TP receptors), is generated due to the diverted arachidonic acid metabolism pathway [108]. Therefore, the combined use of TxA2 synthase inhibitor and TP receptor antagonist could be more effective in the treatment of allergic asthma.…”
Section: Antiplatelet Therapies For Asthma Controlmentioning
confidence: 99%
“…In the context of continued discoveries of GPCRs in bronchoconstriction vs. dilation, the complex roles of prostaglandins (PGs) in the airway (99,215,372,447,455,586) are being teased out. Products of the COX pathway in arachidonic acid metabolism, the five primary PGs (PGD 2 , PGE 3 , PGF 2 , PGI 2 , and TXA 2 ), all signal through distinct GPCRs.…”
Section: L1117 Smooth Muscle and Beyondmentioning
confidence: 99%
“…[ 19 20 ] Studies from Japan have reported that thromboxane modulators may have role as an add-on therapy to inhaled corticosteroids in the event of poor response to corticosteroids, in the setting of chronic asthma. [ 4 9 ] However, to the best of our knowledge, this group of drugs does not appear to have been tested in acute asthma setting. In our study, ozagrel did not demonstrate any benefit over and above the standard treatment of acute asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our endeavor in this study was to address the issues of any usefulness of montelukast and ozagrel in acute asthma. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%